EPID-02. ANTIBODY REACTIVITY TO VARICELLA-ZOSTER VIRUS AND THREE OTHER HERPESVIRUSES AND SURVIVAL IN ADULTS WITH GLIOMA. (14th November 2022) - Guerra, Geno; Francis, Stephen; McCoy, Lucie; Hansen, Helen; Rice, Terri; Molinaro, Annette; Wiencke, John; Wrensch, Margaret
Abstract: Measures of Varicella-Zoster virus (VZV) have been consistently inversely associated with glioma risk, but the association with glioma survival has not been investigated. In this study we analyzed overall survival of individuals with glioma in relation to measured levels of antibodies to 4 common viral infections, measured post-diagnosis. METHODS: We utilized immunoglobulin G (IgG) antibody measurements to VZV, Epstein-Barr virus (EBV), herpes simplex virus (HSV), and cytomegalovirus (CMV), collected from 1378 patients newly enrolled in the UCSF Adult Glioma Study between 1991-2010. Blood was obtained a median of 3 months post diagnostic surgery. Subject follow-up for survival is ongoing. The associations of IgG levels with overall survival were estimated using Cox models adjusted for age, sex, race, type of surgery, dexamethasone usage, and stratified by tumor grade. RESULTS: The 1378 glioma patients studied had median survival of 2.1 years. VZV antibody seropositivity was associated with improved survival outcomes (Hazard ratio, HR = 0.70, 95% Confidence Interval 0.54-0.90, p = 0.0061), with a grade-IV specific association (HR=0.65, 0.48-0.87, p=0.0046). Amongst VZV seropositive cases, those in the bottom quartile of measured seroreactivity had significantly worse survival outcomes as compared to the upper three quartiles (HR = 1.31, 1.13-1.52, p = 0.0003). Antibody seropositivity to EBV was also associated with improved survival times (HR = 0.71, 0.53-0.96, p = 0.028). Antibody response to two other common viruses (CMV, HSV) were not associated with glioma survival (p = 0.213, p = 0.215, respectively). CONCLUSION: This is the first study, to our knowledge, to associate virus-specific antibody levels with survival amongst glioma patients. These associations do not appear to be due to general tumor-induce immune suppression. Our results controlled for dexamethasone usage, a known immunosuppressor. IgG measurements were taken post-glioma diagnosis, therefore further study is needed to determine the direction of causation, and if anti-herpesvirus treatment, such as VZV vaccination, might be beneficial for glioma prognosis.